Fabrication and Characterization of CNT-Based Smart Tips for Synchrotron Assisted STM. (18th August 2015) - Yan, Hui; Cummings, Marvin; Camino, Fernando; Xu, Weihe; Lu, Ming; Tong, Xiao; Shirato, Nozomi; Rosenmann, Daniel; Rose, Volker; Nazaretski, Evgeny
Abstract : Determination of chemical composition along with imaging at the atomic level provides critical information towards fundamental understanding of the surface of materials and, hence, yields the capability to design new materials by tailoring their ultimate functionalities. Synchrotron X-ray assisted scanning tunneling microscopy (SX-STM) is a promising new technique to achieve real space chemically specific atomic mapping. Chemical sensitivity of SX-STM relies on excitation of core electrons by incident X-rays when their energy is tuned to an absorption edge of a particular element. However, along with core-level electrons, photoelectrons are also excited, which yield additional current and interfere with the tunneling current. To reduce the background photoelectron current and to improve ultimate resolution of SX-STM, we have developed and fabricated multiwalled carbon nanotubes (MWCNT) based "smart tips" using plasma enhanced chemical vapor deposition and focused ion beam milling. The newly developed CNT-based smart tips, characterized step by step by scanning electron microscopy (SEM) during the fabrication process, demonstrate good performance and provide opportunity for realizing atomic chemical mapping.